The financial and non-financial elements in the franchise disclosure document for a new franchise system - Mohd Harif, Mohd Amy Azhar (2011)
Franchising is the fastest growing method of doing business. In Malaysia in particular, franchising has been aggressively promoted by the government since the early 1990s. However, there is little academic research to guide or regulate industry practices. Thus, this research investigated the financial and non financial elements that should be in the franchise disclosure document. This research used action research methodology to for this purpose and benefited from the involvement and co-operation from the government department that regulates franchise industry in Malaysia. Three main action research cycles (with two mini-action cycles for each main cycle) were conducted with three new franchise systems seeking to register with the Registrar of Franchise. In order to triangulate the findings of the action research, the findings were presented them at the National Franchise Workshop. Final results show that the franchise disclosure document should comprise 25 elements: 9 financial and 16 non-financial elements. The Registrar of Franchise in Malaysia has since adopted these elements and requires these to be included in the franchise disclosure document for a new franchise system.